Retrospective Study: The Use of Chemical Peeling with A Modiï¬ed Jessners in Melasma Patients - Effendy, Zada Febrial; Setyaningrum, Trisniartami (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: Melasma is a hipermelanosis that lead to brownish or brownish-grey discoloration on the face. Chemical peeling is one ofÂ  the additional therapy for melasma. The right indication using modiï¬ed Jessners solution give a good result for melasma. Purpose: To evaluateÂ  new patients of melasma which underwent chemical peeling therapy with Jessners modiï¬ed in Medical Cosmetics Division of Dermato-Venerology Department,Â  Dr. Soetomo General Hospital Surabaya in 2010-2013. Methods: Retrospective study of the new medical records of melasma, including the number of patients, age distribution, gender, occupation, risk factors, history of previous treatment, duration of treatment, location of melasma, color of melasma, size of melasma, additional test results, type of melasma, melasma side effects, the use of priming, chemical peeling, post-peels, and follow up. Results: The number of new patients with melasma which underwent chemical peeling were 108 patients from 1544 (14.2%) new melasma patientsÂ  visiting Cosmetics Division of Dermato-Venerology Department, Dr. Soetomo General Hospital. All patients were women with the largest age group of 40-49 years, which is 66 (61.1%) patients. Highest risk factor was a mixture of sun exposure and use of cosmetics product, which is 56 (51.8%) patients. Most melasma type was mixed melasma. Patients who used a Jessners modiï¬ed peels, mostly used alpha hydoxy acid (AHA), Kligmans formula, and tretinoin as priming as many as 28 (25.9%) patients and majority post-peels used a moisturizer, sunblock, hydrocortisone, which is 57 (52.8%) patients. Erythema after peeling were complained from 50Â  (46.3% ) patients. Conclusion: The use of chemical peeling is one of adjunctive therapy in melasma with a proper diagnosis.Keywords: melasma, chemical peeling, modiï¬ed Jessners, retrospective.